2016
DOI: 10.1021/acschembio.5b00909
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Screen Exposes mTOR Signaling Pathway Involvement in Radiation-Induced Apoptosis

Abstract: Individuals are at risk of exposure to acute ionizing radiation (IR) from a nuclear accident or terrorism, but we lack effective therapies to mitigate the lethal IR effects. In the current study, we exploited an optimized, cell-based, high throughput screening assay to interrogate a small molecule library comprising 3437 known pharmacologically active compounds for mitigation against IR-induced apoptosis. Thirty-three library compounds significantly reduced apoptosis when administered 1 h after 4 Gy IR. Two- o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The role of mTOR in determining radiation response is not fully understood and is likely dependent on many factors such as cell type, microenvironment, and competing extracellular or intracellular signals ( Figure 5 ). Rapamycin and other mTOR inhibitors have antitumor activity and act as radiosensitizers in many solid tumors [ 86 , 117 , 118 , 119 , 120 , 121 , 122 ]; however, they are also radioprotectors in several normal cell types in vitro [ 72 , 123 , 124 ]. The precise role played by each mTOR complex is not clear.…”
Section: Mtor-dependent Molecular Mechanisms That Promote Pulmonarmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of mTOR in determining radiation response is not fully understood and is likely dependent on many factors such as cell type, microenvironment, and competing extracellular or intracellular signals ( Figure 5 ). Rapamycin and other mTOR inhibitors have antitumor activity and act as radiosensitizers in many solid tumors [ 86 , 117 , 118 , 119 , 120 , 121 , 122 ]; however, they are also radioprotectors in several normal cell types in vitro [ 72 , 123 , 124 ]. The precise role played by each mTOR complex is not clear.…”
Section: Mtor-dependent Molecular Mechanisms That Promote Pulmonarmentioning
confidence: 99%
“…Intracellular and/or extracellular stressors such as hypoxia or DNA damage generally downregulate mTORC1, limiting cell growth and metabolic functions [ 78 ]. However, the activation of mTOR in periods of stress—such as after radiation exposure—can encourage accelerated cell death rather than cell cycle arrest, as essential nutrients may not be available to the cell [ 123 , 125 , 126 ]. Cancer cells are often capable of surviving in abnormal and harsh conditions such as hypoxic and low nutrient conditions and therefore may have altered mTOR regulators or a shift in dependence on the PI3K/AKT/mTOR pathway.…”
Section: Mtor-dependent Molecular Mechanisms That Promote Pulmonarmentioning
confidence: 99%
“…Activation of intracellular apoptotic signaling pathways During radiotherapy, radiation-induced DNA damage can lead to cell death by activating different cellular events, 62 and DNA damage can cause cell death by activating downstream signaling pathways such as p53, MAPKs and AKT. 63 We investigate the expression and phosphorylation of the DNA damage-related proteins in the treated cells, including histone and p53.…”
Section: Activation Of Ros-mediated Signaling Pathwaysmentioning
confidence: 99%
“…We observed that high cytoplasmic raptor expression indicated a worse prognosis, a finding that was consistent with the role of increased oncogenic cytoplasmic mTORC1 signaling in breast cancer. Knock-down of either raptor or rictor mitigated the effect of radiation-induced apoptosis, by decreasing entry into S-phase and inducing cell cycle arrest in both G1 and G2 phases [ 34 ]. This is in line with the proposed function of raptor as a general oncogenic protein as we observed cytoplasmic raptor association with poor breast cancer outcome.…”
Section: Discussionmentioning
confidence: 99%